(untitled) (Journal of Hama University, 2024)
Although the effect of semi-rigid steel beam-to-column connections on the behavior of steel frames and their substantial economic benefits are recognized nowadays, many structural analyses still consider some parameters related to the components of connections. For that reasons, there is need to be able the generate moment-rotation responses of semi-rigid connections that can be used for analysis and design proposes. Characteristic of the joints can be found using FEM models. The objective of the analysis was to find moment-rotation curves for end-plate connections. The analyzed splices were shaped considering typical recommendations for such connections. Numerical elastic-plastic 3D finite models were performed in order to establish a numerical analysis method for evaluating deformation of extended end-plate-beam-to-column joint for varying thickness of end plates and diameter of bolts. The study confirmed the influence of thickness of end plates and diameter of bolts on moment-rotation curves for analyzing joints and proved that the FE technique was capable of prediction connection response to an acceptable degree of accuracy. The results can be used in advanced structural analysis of beams and frames.